Utilización de medios probatorios en los procedimientos disciplinarios en el sector educación y su afectación al debido procedimiento - Uriol Rubio, John Fredy (2014)
The Constitution and the law recognize the right of the administration to provide evidence regarding the facts means that state; however, the current trend is that the person taking the burden of proof is who is in a better position to prove a fact in this case the administration. The authority should have full conviction of their decisions when deciding. Through this work entitled "USE OF PROOF MEDIA IN DISCIPLINARY PROCEEDINGS IN THE EDUCATION SECTOR INVOLVEMENT AND DUE PROCESS " try to explain the problem in the education sector in the exercise of sanctioning powers, where there is evidence sufficient and proper use of the evidence from the research commissions within the statement of disciplinary proceedings. The administration, in most cases, simplify the administrative procedure in a transfer of charges and just wait for his acquittal in writing (if any) to issue the final report, and thus the appropriate sanction, without going beyond its role probation, to fully verify facts and pursuant to this, reasons for its decisions, a situation that obviously affects due process. This work will underpin the problem and warned as a result of its doctrinal, normative and practical professional analysis, present the corresponding recommendations to counter their hypothesis, they emphasize that the intention of strengthening the principles of disciplinary law and contribute to its development in the function public, respecting and highlighting the importance of proper exercise of sanctioning powers of the State.